Discovery of a shoal-controlled karst dolomite reservoir in the Middle Permian Qixia Formation, northwestern Sichuan Basin, Southwest China - Di Xiao; Benjian Zhang; Xiucheng Tan; Hong Liu; Jirong Xie; Lichao Wang; Xun Yang; Teng Ma (Energy Exploration & Exploitation, 2018)
The dolomites of the Middle Permian Qixia Formation have been important targets of natural gas exploration in the Sichuan Basin for decades. However, more and more exploration and research indicate that the formation of the reservoir might be related to karstification. To testify this hypothesis, we conduct comprehensive outcrop, core, and logging analyses based on a case study in the representative northwestern Sichuan Basin, which has obtained exploration breakthroughs recently. Results show that the Qixia dolomite reservoirs are mainly developed within fine-crystalline dolomites formed by a series of diagenetic modifications, which can be further divided into three types according to the macro- and micro-occurrences of dolomites: euhedral-subhedral crystalline dolomites in the quasi-stratiform karst system (mean porosity and permeability is 3.51% and 3.11 mD, respectively), euhedral-subhedral crystalline dolomites in the leopard porphyritic karst system (mean porosity and permeability is 3.36% and 1.22 mD, respectively), and allotriomorphic mosaic crystalline dolomites with residual parent rock fabrics (mean porosity and permeability is 0.94% and 0.92 mD, respectively). Their reservoir qualities decrease along the order. The formation mechanism of the reservoir is shoal-controlled karst. The preservation of residual intergranular pores within the thin-layer grainstones of shoal facies provides favorable channels for karst water. In the vadose zone, the heterogeneous dissolution within grainstones leads to the formation of leopard porphyritic dissolution features. In the phreatic zone, the karst water flowing along the stratiform grainstones results in the formation of quasi-stratiform dissolution features. The karst system is filled with loose carbonate sands and gravels, whose reservoir properties are far superior to parent rocks, and they can provide migration channels for the hydrothermal fluids with rich Mg 2+ in the burial stage. The replacement of hydrothermal fluid results in the redistribution of pores and vugs of inter-fillings within karst system and the formation of intercrystalline pores and residual vugs, but the reservoir space of parent rocks keeps the same as the original condition. Therefore, the exploration of the Qixia dolomite reservoir should be changed to shoal-controlled karst.